2015
DOI: 10.1002/oby.21072
|View full text |Cite
|
Sign up to set email alerts
|

Earlier onset of diabesity‐Induced adverse cardiac remodeling in female compared to male mice

Abstract: Objective: Emerging evidence suggests female type 2 diabetes (T2DM) patients may fare worse than males with respect to cardiovascular complications. Hence the impact of sex on relative progression of left ventricular (LV) remodeling in obese db/db mice was characterized. Methods: The changes in parameters of LV hypertrophy (heart weight, pro-hypertrophic gene expression, cardiomyocyte size) and fibrosis (LV collagen deposition and oxidative stress), in parallel with body weight and blood glucose and lipid prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 41 publications
3
20
0
Order By: Relevance
“…In exploratory analyses, we found complex sex- and race-based heterogeneity in cardiac structural associations with pericardial fat, including greater hypertrophy and concentric LV remodeling in females, and a non-linear relationship between pericardial fat and LV function in African Americans. While these observations arise from secondary analyses and require confirmation in larger, emerging multi-ethnic cohorts worldwide, they are concordant with prior laboratory and clinical research: in animal models of obesity and diabetes, cardiac remodeling is observed early in the pathogenesis of obesity/diabetes 41 , and HF with preserved LV ejection fraction risk is higher specifically in older, obese women 42 . Furthermore, African-Americans harbor a disproportionate risk of subclinical LV dysfunction 43 and higher CVD-related mortality 44 .…”
Section: Discussionsupporting
confidence: 71%
“…In exploratory analyses, we found complex sex- and race-based heterogeneity in cardiac structural associations with pericardial fat, including greater hypertrophy and concentric LV remodeling in females, and a non-linear relationship between pericardial fat and LV function in African Americans. While these observations arise from secondary analyses and require confirmation in larger, emerging multi-ethnic cohorts worldwide, they are concordant with prior laboratory and clinical research: in animal models of obesity and diabetes, cardiac remodeling is observed early in the pathogenesis of obesity/diabetes 41 , and HF with preserved LV ejection fraction risk is higher specifically in older, obese women 42 . Furthermore, African-Americans harbor a disproportionate risk of subclinical LV dysfunction 43 and higher CVD-related mortality 44 .…”
Section: Discussionsupporting
confidence: 71%
“…However, diabetes induced cardiac remodeling in mice was increased in females at an earlier stage than in males. This was measured by prohypertrophic and prooxidant gene expression as well as cardiomyocyte size ( 287 ).…”
Section: Cardiovascular Complicationsmentioning
confidence: 99%
“…Db/db mouse is a model of T2DM with leptin receptor insensitivity characterized by significant obesity, fasting hyperglycemia, hyperinsulinemia, and insulin resistance. It also develops changes in cardiac structure and function similar to those in T2DM patients . Recent studies have confirmed that functional and morphological alterations in db/db hearts are consistent with DCM …”
Section: Introductionmentioning
confidence: 74%
“…It also develops changes in cardiac structure and function similar to those in T2DM patients. 16 Recent studies have confirmed that functional and morphological alterations in db/db hearts are consistent with DCM. 17,18 In this study, we aimed to investigate the association of GRK2 with early DCM by estimating the expression of GRKs both in the myocardium of diabetic mice and in the PBMCs of patients with early DCM.…”
Section: Introductionmentioning
confidence: 91%